Spray‐Coating Magnetic Thin Hybrid Films of PS‐b‐PNIPAM and Magnetite Nanoparticles. (18th February 2019) - Xia, Senlin; Song, Lin; Hohn, Nuri; Wang, Kun; Grott, Sebastian; Opel, Matthias; Schwartzkopf, Matthias; Roth, Stephan V.; Müller‐Buschbaum, Peter
Abstract: Spray coating is employed to fabricate magnetic thin films composed of the diblock copolymer polystyrene‐ block ‐poly( N ‐isopropylacrylamide) and Fe3 O4 magnetic nanoparticles (MNPs) functionalized with hydrophobic coatings. The kinetics of structure formation of the hybrid films is followed in situ with grazing incidence small angle X‐ray scattering during the spray deposition. To gain a better understanding of the influence of MNPs on the overall structure formation, the pure polymer film is also deposited as a reference via an identical spray protocol. At the initial spraying stage, the hybrid film (containing 2 wt% of MNPs) exhibits a faster formation process of a complete film as compared to the reference. The existence of MNPs depresses the dewetting behavior of polymer films on the substrate at macroscale and simultaneously alters the polymer microphase separation structure orientation from parallel to vertical. As spraying proceeds, MNPs aggregate into agglomerates with increasing sizes. After the spray deposition is finished, both samples gradually reach an equilibrium state and magnetic films with stable structures are achieved in the end. Superconducting quantum interference device investigation reveals the superparamagnetic property of the sprayed hybrid film. Consequently, potential application of sprayed films in fields such as magnetic sensors or data storage appears highly promising. Abstract : Magnetic films composed of polystyrene‐ block ‐poly( N ‐isopropylacrylamide) and magnetite nanoparticles (NPs) are fabricated by spray deposition. The kinetic structure evolution of the magnetic films is followed via in situ grazing incidence small angle X‐ray scattering. Compared with NP‐free polymer film, a faster formation process of a complete film and an alteration of the nanostructure orientation are observed for the hybrid one.